2018
DOI: 10.1111/jace.15798
|View full text |Cite
|
Sign up to set email alerts
|

Potential thermal barrier coating materials: RE3NbO7 (RE=La, Nd, Sm, Eu, Gd, Dy) ceramics

Abstract: In this work, RE3NbO7 ceramics are synthesized via solid‐state reaction and the phase structure is characterized by X‐ray diffraction and Raman spectroscopy. The relationship between crystal structure and thermophysical properties is determined. Except Sm3NbO7, each RE3NbO7 exhibits excellent high‐temperature phase stability. The thermal expansion coefficients increase with the decreasing RE3+ ionic radius, which depends on the decreasing crystal lattice energy and the maximum value reaches 11.0 × 10−6 K−1 at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(10 citation statements)
references
References 42 publications
0
9
0
1
Order By: Relevance
“…The H v of RE‐based niobates HEOs with disordered defect fluorite structure is 8∼10 GPa approximately, which is higher than that with orthorhombic structure [81] . In addition, the H v values of 5RE 3 NbO 7 and 4RE 3 NbO 7 are about 9.51 and 9.37 GPa, respectively, stronger than RE 3 NbO 7 (8.12∼9.39 GPa).…”
Section: Properties and Applicationsmentioning
confidence: 89%
See 1 more Smart Citation
“…The H v of RE‐based niobates HEOs with disordered defect fluorite structure is 8∼10 GPa approximately, which is higher than that with orthorhombic structure [81] . In addition, the H v values of 5RE 3 NbO 7 and 4RE 3 NbO 7 are about 9.51 and 9.37 GPa, respectively, stronger than RE 3 NbO 7 (8.12∼9.39 GPa).…”
Section: Properties and Applicationsmentioning
confidence: 89%
“…The H v of RE-based niobates HEOs with disordered defect fluorite structure is 8 ~10 GPa approximately, which is higher than that with orthorhombic structure. [81] In addition, the H v values of 5RE 3 NbO 7 and 4RE 3 NbO 7 are about 9.51 and 9.37 GPa, respectively, stronger than RE 3 NbO 7 (8.12 9.39 GPa). Since the increase of entropy has little effect on chemical bond strength, the hardness of the multicomponent HEO should be enhanced after solid-solution strengthening and grain refinement based on the Hall-Petch relationship.…”
Section: Mechanical Propertiesmentioning
confidence: 92%
“…where a 3 is the volume per atom, v is the transverse wave speed, ω is the phonon frequency, c is the defect concentration per atom, J is the Gruneisen parameter, and γ is the average atomic mass. Considering Equations ( 10), (14), and (15), it is clear that a larger ΔM (or ΔR) results in a lower mean free path of phonons and lower thermal conductivity.…”
Section: Thermophysical Propertiesmentioning
confidence: 99%
“…Rost et al 10 discovered an entropy-stabilized single-phase rock-salt-structured oxide, (Mg 0.2 Co 0.2 Ni 0.2 Zn 0.2 Cu 0.2 )O, which first extended the concept of HE materials from the field of alloys to that of ceramics. Subsequently, multicomponent systems of high-entropy ceramics (HECs) have emerged, including HE rare-earth oxides, such as zirconates, 11 ceriates, 12 tantalates, 13 niobates, 14 aluminates, 15 and HE borides, 16 carbides, 17,18 nitrides, 19 silicides, 20 and other compounds. 21,22 HECs exhibit better thermal and mechanical properties, high-temperature phase stability, and high-temperature corrosion resistance than single cation ceramics owing to their HE effects.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that high entropy carbides, oxides, and other high entropy materials similarly demonstrate lower thermal conductivity because of high entropy effects. [8][9][10][11][12] Lately, Chen et al 13 and Yang et al 14 studied the thermal properties of rare-earth niobates (RE 3 NbO 7 ). They found that the thermal conductivities of binary niobates were 1-1.8 W/m⋅K, close to its theoretical minimum limit and that of SiO 2 (∼1.36 W/m⋅K).…”
Section: Introductionmentioning
confidence: 99%